1975
DOI: 10.1007/bf02532443
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 3, 6, 9, 12, 15‐octadecapentaenoic acid in laboratory‐cultured photosynthetic dinoflagellates

Abstract: Polar and nonpolar chromatograms of fatty acid methyl esters derived from 11 species of photosynthetic, marine dinoflagellates cultured in modified Erd-Schrieber medium contained a component (4-23%) not identifiable by conventional graphic or arithmetic methods. Hydrogenation followed by gas liquid chromatography of the product showed the unknown component to be a straight chained 18 carbon fatty acid methyl ester. Chemical (ch4) ionization mass spectrometry of the isolated ester gave a spectrum characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…Dinophyceae (dinoflagellates), Haptophyceae (coccolithophorids), Prymnosiophyceae (Phaeocystis spp. ), Chlorophyceae and Prasinophyceae (green microalgae) are rich in C18 polyunsaturated acid (Joseph 1975, Volkman et al 1981, Claustre et al 1989, Dunstan et al 1992. Myristic acid (14:O) is a prominent fatty acid in diatoms and coccolithophorids (Ackman et al 1964, 1968, Volkman et al 1981 and is usually absent from the polar lipids of pelagic consumers (Sargent & Whittle 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Dinophyceae (dinoflagellates), Haptophyceae (coccolithophorids), Prymnosiophyceae (Phaeocystis spp. ), Chlorophyceae and Prasinophyceae (green microalgae) are rich in C18 polyunsaturated acid (Joseph 1975, Volkman et al 1981, Claustre et al 1989, Dunstan et al 1992. Myristic acid (14:O) is a prominent fatty acid in diatoms and coccolithophorids (Ackman et al 1964, 1968, Volkman et al 1981 and is usually absent from the polar lipids of pelagic consumers (Sargent & Whittle 1981).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 16:4n-1, 18:5n-3 or 20:1n-9 and 22:1n-13+11 fatty acids are characteristics of plankton assemblages dominated by diatoms, dinoflagellates (some Haptophycae) and Calanus spp. type copepods, respectively (Ackman et al 1964, Joseph 1975, Mayzaud et al 1976, Pascal & Ackman 1976. Ratios among fatty acids have also been used to clarify the dominant trophic interactions between zooplankton and phytoplankton or zooplankton and higher trophic levels.…”
Section: Use Of Fatty Alcohol and Fatty Acid Patterns In Trophic Studiesmentioning
confidence: 99%
“…Euglena gracilis is the typical phytoflagellate in which relatively high concentrations of arachidonic and docosapentaenoic acids have been found, including in dark-grown cells (Nichols and Appleby 1969;Fouche and Coniglio 1977). The occurrence of octadecapentaeonic acid (18:5 oJ3) appears be a useful taxonomic criterion for classifying marine plankton as dinoflagellates (Joseph 1975;Mayzand et al 1976;Jones et al 1983). Joseph (1975) demonstrated that 11 species of laboratory-cultured, photosynthetic dinoflagellates contained 4-23% of this fatty acid, which, however, was produced by 2-carbon-chain shortening of eicosapentaenoic acid (20:5 o~3).…”
Section: Microalgaementioning
confidence: 99%
“…The occurrence of octadecapentaeonic acid (18:5 oJ3) appears be a useful taxonomic criterion for classifying marine plankton as dinoflagellates (Joseph 1975;Mayzand et al 1976;Jones et al 1983). Joseph (1975) demonstrated that 11 species of laboratory-cultured, photosynthetic dinoflagellates contained 4-23% of this fatty acid, which, however, was produced by 2-carbon-chain shortening of eicosapentaenoic acid (20:5 o~3). Other polyunsaturated fatty acids have been detected in dinoflagellates (Harvey et al 1988).…”
Section: Microalgaementioning
confidence: 99%